Processing Fishery Products for Community Food Security at the East Kutai Regency - Suprianto Suprianto; Eny Heriyati; Anshar Haryasakti; Imanuddin Imanuddin; Rosdianto Rosdianto (Altifani Journal: International Journal of Community Engagement, 2023)
In order to increase the utilization of fisheries potential, it is necessary to diversify fish processing. East Kutai is a district that has the potential to produce fisheries, especially from fishing. The catch of sea fish and freshwater fish in East Kutai Regency in 2020 was 5,294 tons. Diversifying fish processing is one means of increasing community food security. The STIPER East Kutai Marine Science Study Program plays a role in helping the government to increase food security through exhibition activities at the "food and nutrition month" event with the theme of sustainable food security organized by the East Kutai Food Security Service. This activity is carried out as a form of community service in carrying out one of the Tri Dharmas of Higher Education. Processing of tuna and shrimp nuggets as a diversified fish processing product is presented to the public. At this event, people were also distributed selebarans about how to process fish into processed products. Community Service activities carried out for four days ran smoothly. The tuna and shrimp nuggets products presented were also subjected to organoleptic testing by exhibition visitors. Exhibition activities are very effective in disseminating knowledge on campus to be disseminated to the community.